LEGAL PROTECTION FOR WITNESS UNDER THE WITNESS AND VICTIM PROTECTION LAW - Damendra, Gede Agus; P. Perbawa, Kt Sukowati Lanang; Saraswati, Putu Sekarwangi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Indonesia’s legal system provides a robust framework for protecting witnesses. In criminal cases, justice and legal certainty are ensured while also prioritizing the safety and well-being of witnesses. This study examines the regulation of legal protection for witnesses and victims under the Witness and Victim Protection Law and assesses if the Law has been effective in providing justice and legal certainty. The research method employed normative legal research. The Criminal Procedure Code (KUHAP) inadequately protects witnesses, as revealed by the study. The Witness and Victim Protection Law clearly outlines the rights of witnesses and victims of criminal acts in specific cases, as determined by the Witness and Victim Protection Agency (LPSK). In addition, the law requires that victims of gross human rights crimes receive compensation from the state. According to Government Regulation No. 44/2008, the state provides compensation when the perpetrators are unable to fully meet their responsibility.Keywords: Legal Protection, Witness, Victim